UNDERWEIGHT AND MORBIDITY STATUS AMONG UNDER FIVE YEARS CHILDREN IN SURABAYA - Triska Susila Nindya; Lailatul Muniroh (UNEJ e-Proceeding)
Under five years old children is one of the group thatvulnerable to under nutrition, moreover this agegroup also susceptible to infectious disease due totheir immunity and their activity related to exposureof infectious disease. To achieve optimal growth, achildren must obtain adequate dietary intake,optimal care practice that include appropriatefeeding practices and less frequent of infectiousdisease (Black et al, 2008). Inadequate food intaketo Undernutrition among under five childrenbecome important issue since it can affect shortterm and also long term that go beyond child hood(Neufeld and Osendarp, 2014). Indonesia BasicHealth Survey revealed there was fluctuation ofunderweight prevalence from 18.4% in 2007,decreased to 17.9% in 2010 and increased to 19.6%in 2013 (Indonesia Basic Health Survey, 2013). Thereis a strong evidence that undernutrition thatoccurred during the first two years of life contributeto the increasing risk of non communicable diseasein the later life (Victora et al, 2008). Communicabledisease is one of the factors that contribute tonutritional status, particularly underweight inchildren since underweight is the indicator thatreflect an acute disturbance of nutritional status.Communicable diseases that often occur in childrenare diarrhea and upper respiratory infecti on. Indeveloping countries, diarrhea contributes to thechildhood morbidity and mortality, as it estimatedthat 1.5 million child die to diarrhea per year (Roy etal, 2011). There is a bidirectional relationship ofdiarrhea and malnutrition in children with themechanism of diarrhea episodes lead to anorexia,absorptive function impairment, the damage ofmucosal and the increase need of nutrients (Brown,2003). Malnutrition also increase the incidence andseverity of acute respiratory infection throughmechanism of immunity impairment, particularly incellular immunity (Bhutta et al, 1998). This studyaimed to analyze the association of underweight andmorbidity of diarrhea and acute respiratory infectionin under five years old children.